Predicting outcome in 259 fetuses with agenesis of ductus venosus – a multicenter experience and systematic review of the literature*. (16th November 2016) - Moaddab, Amirhossein; Tonni, Gabriele; Grisolia, Gianpaolo; Bonasoni, Maria Paola; Araujo Júnior, Edward; Rolo, Lilliam Cristine; Prefumo, Federico; de la Fuente, Sergio; Sepulveda, Waldo; Ayres, Nancy; Ruano, Rodrigo
Abstract: Objective : To evaluate prenatal predictors of postnatal survival in fetuses with agenesis of ductus venosus (ADV). Methods : This retrospective study reviewed our experience and the literature between 1991 and 2015. Prenatal findings were evaluated and perinatal morbidity and mortality was documented. Results : A total of 259 cases were included in the present analysis from our centers and 49 published studies (15 patients from our retrospective cohort review and 244 from literature review). The intrahepatic and extrahepatic shunts were present in 32.0% (73/226) and 67.7% (153/226), respectively. Cardiomegaly ( n = 64/259, 24.7%), hydrops ( n = 31/259, 12.0%) and amniotic fluid abnormalities ( n = 22/259, 8.5%) were among the most frequent initial ultrasound findings. One hundred and forty-seven fetuses (56.8%) had ADV without structural anomalies while 112 (43.2%) had associated anomalies (cardiac anomalies ( n = 66), extra-cardiac anomalies ( n = 19) and both cardiac and extra-cardiac anomalies ( n = 27)). The mean gestational age (GA) at ultrasound diagnosis was 22.9 ± 6.9 weeks while the mean GA at delivery was 34 ± 7.5 weeks. The overall neonatal survival was 57.1% ( n = 148/259). The following factors were associated with survival: advanced maternal age, earlier GA at diagnosis, prematurity, increased nuchal translucency, pericardial effusion, associated cardiac defects (especially AVSD), chromosomal abnormalities, hydrops, hygroma and limb anomalies. Conclusion : Fetal hydrops, the presence of associated congenital anomalies and premature delivery are associated with poor prognosis in fetuses with ADV.